Ketidaksesuaian Dosis dan Interval Pemberian Antibiotik pada Lansia di Bangsal Penyakit Dalam RSUD dr Moewardi Solo serta Gambaran Timbulnya Efek Samping yang Merugikan - Rita Septiana; Risma Sakti Pambudi (Fakultas Farmasi Universitas Setia Budi, 2019)
Aging causes a decrease in renal blood flow velocity and clearance values ​​related to renal filtration function. A decrease in kidney filtration function results in a decrease in the ability of drug elimination so that the drug and its metabolites tend to accumulate in the blood. The dose of certain antibiotics must be adjusted to the patient's kidney function. Clinical estimates of kidney filtration function are expressed in terms of creatinine clearance (CrCl). This study aims to determine the percentage of suitability of the dose and interval of antibiotic administration with the CrCl value of elderly patients and to see description of the side effects arising from the administration of antibiotics. This research was observational with data retrospective retrieval of medical records. The subjects of the study were elderly patients who were hospitalized in the ward ward in dr. Moewardi Solo Hospital in the period January - May 2019 , ≥ 60 years aged with a diagnosis of Pneumonia, Urinary Tract Infection (UTI), Cellulitis and sepsis with complete medical record data. The antibiotics evaluated are all antibiotics given to the patient while being treated. The results showed the suitability of the dose and interval of antibiotic administration with the CrCl value of elderly patients hospitalized in the disease ward in RSUD Dr. Moewardi Solo for the period January-May 2019 was 63.35%, the incidence of side effects arising from the administration of antibiotics was nausea and vomiting (10 patients ) and diarrhea (4 patients).